2014
DOI: 10.1007/s00284-014-0676-7
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba T4, T5 and T11 Isolated From Mineral Water Bottles in Southern Brazil

Abstract: Acanthamoeba is a protist potential pathogen, capable of causing a blinding keratitis in contact lens wearers and disseminated infection, leading to granulomatous amebic encephalitis in immunocompromised individuals. This amoeba is a ubiquitous organism that has been isolated from various domestic water systems, such as cooling towers and hospital water networks. The objective of this work was to investigate the presence of Acanthamoeba in mineral water bottles marketed in Porto Alegre, southern Brazil. Positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…Fallah et al [59] published for the first time the presence of Acanthamoeba T3, T4, T11 and T5 in tap water sources from a touristic region in Iran. In another study about the distribution of Acanthamoeba genotypes in water samples from mineral water bottles in Porto Alegre, southern Brazil, the authors reported genotype T5 as the most common among the sequences analyzed [60]. Finally, Sente et al (2016) [61] reported the isolation of Acanthamoeba in 36 domestic water sources (42.9%) in the Queen Elizabeth Protected Area, Uganda, including the genotypes T1, T2, T4, T5, T6 and T11.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fallah et al [59] published for the first time the presence of Acanthamoeba T3, T4, T11 and T5 in tap water sources from a touristic region in Iran. In another study about the distribution of Acanthamoeba genotypes in water samples from mineral water bottles in Porto Alegre, southern Brazil, the authors reported genotype T5 as the most common among the sequences analyzed [60]. Finally, Sente et al (2016) [61] reported the isolation of Acanthamoeba in 36 domestic water sources (42.9%) in the Queen Elizabeth Protected Area, Uganda, including the genotypes T1, T2, T4, T5, T6 and T11.…”
Section: Discussionmentioning
confidence: 96%
“…Zymographic assays were performed as previously described by Herron et al [65]. Briefly, protein extracts of trophozoites and ACM were subjected to electrophoresis on SDS-polyacrylamide gels (SDS-PAGE) containing gelatin (1 mg/mL) as described by Castro Artavia et al in 2017 [60]. After the electrophoresis, the gels were washed twice in 1% Triton X-100 (w/v) for 30 min to remove the SDS and incubated overnight at 37 • C in a developing buffer (50 mM Tris-HCl, 10 mM CaCl 2 , pH 8.0), rinsed and then stained with Coomassie brilliant blue R-250 (Bio-Rad Laboratories, California, USA).…”
Section: Determination and Characterization Of Protease Secretion By mentioning
confidence: 99%
“…2). Due to suspicious reports of the contaminated cases in other countries and doubtful production process, the bottles of drinking mineral water are other points being neglected for investigation (Maschio et al 2015;Rivera et al 1981). Unfortunately, in many studies, Acanthamoeba were evaluated and other FLA were ignored (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…De todos estos ambientes el más estudiado es el agua. Se han detectado e identificado FLA en aguas residuales (García et al, 2011;Magnet et al, 2013;Mosteo et al, 2013), potables (Thomas et al, 2008;Delafont et al, 2013;Magnet et al, 2013), de río (Niyyati et al, 2012;Magnet et al, 2013), de pozo (Baquero et al, 2014;Montalbano Di Filippo et al, 2015), recreacionales (Heggie, 2010;Sifuentes et al, 2014;Reyes-Batlle et al, 2017), embotellada (Maschio et al, 2015a) y de uso industrial (Scheikl et al, 2014).…”
Section: Distribuciónunclassified
“…µm (Behniafar et al, 2015). Sin embargo, Maschio et al (2015a) μm, 8-20 μm y 6-30 μm respectivamente (Peralta y Ayala, 2009).…”
Section: Ii31 Procesado De Las Muestras Y Aislamiento De Amebas Deunclassified